2015
DOI: 10.1158/2326-6066.cir-14-0044
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus-Based Vaccine Expressing a Modified Tumor Antigen Induces Potent Tumor-Specific CD8+ T-cell Response and Protects Mice from Melanoma

Abstract: The presence of tumor-infiltrating CD8 þ T cells is associated with tumor regression and better prognosis. Cytomegalovirus (CMV) infection elicits a robust and long-lasting CD8 þ T-cell response, which makes CMV a potentially promising vaccine vector against cancer. In the current study, we used recombinant murine CMV (MCMV) strains as prophylactic and therapeutic vaccines in an aggressive B16 lung metastatic melanoma model. Immunization with MCMV-expressing ovalbumin (OVA) induced a potent OVA-specific CD8 þ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 49 publications
2
60
0
Order By: Relevance
“…CMV-based vectors have shown promising results in diverse infectious and cancer models, but the success of these vaccines is considered T cell mediated (5,55,56). Recently, it has been shown that CMV vectors encoding additional antigens also can induce protective anti-melanoma or anti-tetanus toxin antibodies (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…CMV-based vectors have shown promising results in diverse infectious and cancer models, but the success of these vaccines is considered T cell mediated (5,55,56). Recently, it has been shown that CMV vectors encoding additional antigens also can induce protective anti-melanoma or anti-tetanus toxin antibodies (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…CD4 inflation has been much less studied. In a seminal work, a CD4 T cell response specific for the MCMV m09 [133][134][135][136][137][138][139][140][141][142][143][144][145][146][147] peptide was found to be inflationary (although the size of the response was less impressive than those observed in CD8 inflation), indicating that CD4 T cell responses are diverse and may be an interesting target for immunization [117]. This will be expanded on the section dedicated to CD4 T response.…”
Section: Cellular Response-t Cellsmentioning
confidence: 99%
“…On the other hand, MCMV vectors carrying modified epitopes with increased antigenicity were shown to induce immune responses that are sufficient to provide protection in therapeutic settings. For instance, the MCMV expressing the B16 melanoma antigen gp100 (MCMV-gp100KGP) induced a strong, long-lasting gp100-specific CD8 T-cell response with a durable, polyfunctional phenotype with inflationary kinetics [147]. The modified gp100 (gp100KGP) expressed by MCMV induces stronger cytotoxic T lymphocyte responses [148] than an MCMV vector with the original gp100 epitope.…”
Section: Cellular Response-t Cellsmentioning
confidence: 99%
“…Most recently, a study by Qiu and colleagues described a cytomegalovirus vector expressing modified tumor antigens. The vaccine candidate elicited tumor-specific T-cell responses, protecting mice from melanoma (73). Another promising study used a live attenuated poliovirus type 1 to vaccinate against glioblastoma multiforme (74).…”
Section: Prospects Advantages and Challenges Of Multivalent And Mulmentioning
confidence: 99%